PEMBELAJARAN ZAKAT DENGAN MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SMAN 1 KARANGTENGAH DEMAK - Ahmad Taufik (Islamic University of Indonesia, 2019)
The formulation of the problem of this study is how the learning process, how much improvement in learning outcomes, and changes in behavior of students with interactive multimedia in students of class X.IPA.4 SMAN 1 Karangtengah Demak semester 1 of the school year 2017/2018 The research approach is based on classroom action research (CAR). PTK is carried out in two cycles. There is an increase in the completeness of student learning outcomes. The daily repetition rate before the action research (Pre PTK) 67.25 rose to 74.25 in the first cycle and 80.50 in the second cycle. Percentage of completeness before PTK 63.33% (complete 19 students), to 76.67% (completed 23 students) in the first cycle and 96.67% in the second cycle (complete 29 students) of 30 students.Keywords : learn zakat, multimedia interaktif, learning result